PREDICTING BANKRUPTCY USING SPRINGATE, ZMIJEWSKI, AND GROVER AT PT BLUE BIRD TBK PERIOD 2016-2021 - Hernawaty Hernawaty; Maya Macia Sari; Eva Nanda Wulandari (International Journal of Economics and Management Research, 2022)
This quantitative descriptive study aims to determine the Springate Method, Zmijewski Method, and Grover Method to analyze bankruptcy at PT Blue Bird Tbk. The period used in this study is six years, starting from 2016-2021. This research was conducted by taking secondary data from financial statements obtained from the official website www.bluebirdgroup.com. The results showed that using the Springate method in 2016 and 2018 were in a prone area or on the verge of bankruptcy; in 2017, this Company was in good condition, while in 2019-2021, this Company went bankrupt. Using the Zmijewski method shows that in 2016-2021 this Company did not go bankrupt, and the Grover method shows that in 2016-2021 this Company did not go bankrupt. In this case, the Springate method accurately analyzed bankruptcy at PT Blue Bird Tbk.